2019
DOI: 10.3389/fpsyg.2019.00872
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Parental Factors Associated With Developmental Outcomes in Children With Intellectual Disabilities

Abstract: The aim of the study was to examine the relation between demographic variables, parental characteristics, and cognitive, language and motor skills development in children with intellectual disabilities (ID). A sample of 89 children with ID, aged 20–47 months, completed the Bayley Scales of Infant Development to measure cognitive, motor, and linguistic development. Parents were administered questionnaires about demographic information and parental anxiety, depression, parental stress, conjugality and familial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 160 publications
(207 reference statements)
5
53
1
4
Order By: Relevance
“…Our findings in relation to child age and mothers' and fathers' PICCOLO scores only showed a statistically significant positive correlation between child age and scores for the Teaching domain, in mothers, meaning that mothers' teaching behaviors were more frequently observed with older children. These results corroborate those of earlier research on mothers in the general population [17] and mothers with children with a disability [11]. However, none of the fathers' parenting domains was significantly related to child age.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings in relation to child age and mothers' and fathers' PICCOLO scores only showed a statistically significant positive correlation between child age and scores for the Teaching domain, in mothers, meaning that mothers' teaching behaviors were more frequently observed with older children. These results corroborate those of earlier research on mothers in the general population [17] and mothers with children with a disability [11]. However, none of the fathers' parenting domains was significantly related to child age.…”
Section: Discussionsupporting
confidence: 89%
“…We strongly believe that the information on behaviors identified by the PICCOLO could help guide professionals' intervention plans, and also that the Teaching domain is one of the aspects that should be emphasized in young children with IDs and their families when following family capacity-building practices [110]. The PICCOLO has been used with children with identified disabilities such as ID or Autism Spectrum Disorder in large samples in the US [11], Spain [12], Saudi Arabia [111] and Germany and Switzerland [36]. These studies have demonstrated this checklist's strong reliability and predictive validity for families with children with a disability; indeed, in two of these studies the early parenting behaviors measured with the PICCOLO predicted cognitive and language outcomes in children with disabilities [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postnatal factors include traumatic brain injury, infections, convulsive diseases and exposure to neurotoxins, such as lead and mercury 2 . According to previous studies, another variable that is associated with ID is sex; boys have a higher prevalence of ID when compared togirls 5,10,11 . This is due to increased occurrence of X chromosomal mutations12.…”
Section: Introductionmentioning
confidence: 98%